1999
DOI: 10.1038/21682
|View full text |Cite
|
Sign up to set email alerts
|

TRA-1 regulates the cellular distribution of the tra-2 mRNA in C. elegans

Abstract: The GLI protein family is involved in several key developmental processes in both vertebrates and invertebrates. The Drosophila GLI protein, Cubitus interuptus (Ci), regulates segment polarity and wing and leg development. In vertebrates, the GLI proteins control neural, lung, bone and gut development. In the nematode Caenorhabditis elegans, the GLI family member TRA-1 is necessary for normal sexual development. GLI, Ci and TRA-1 each contain five zinc-finger domains and bind the identical DNA sequence. Previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 24 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…There are many other examples of factors and cis-acting sequences that contribute to the regulation of mRNA export. These include the retroviral proteins Rev and Rex, the constitutive transport element of D-type retroviral mRNAs, the Caenorhabditis elegans Zn finger protein TRA-1, the intronless mRNA export elements within the mouse histone H2a mRNA, elements within herpes simplex virus thymidine kinase mRNA and hepatitis B virus RNA, and a retention element within C. elegans splicing factor U2AF mRNA (11,12,14,25,49). In the case of hs mRNA export under stress conditions, however, the evidence in favor of positively acting transport factors and elements is uncertain at best.…”
Section: Discussionmentioning
confidence: 99%
“…There are many other examples of factors and cis-acting sequences that contribute to the regulation of mRNA export. These include the retroviral proteins Rev and Rex, the constitutive transport element of D-type retroviral mRNAs, the Caenorhabditis elegans Zn finger protein TRA-1, the intronless mRNA export elements within the mouse histone H2a mRNA, elements within herpes simplex virus thymidine kinase mRNA and hepatitis B virus RNA, and a retention element within C. elegans splicing factor U2AF mRNA (11,12,14,25,49). In the case of hs mRNA export under stress conditions, however, the evidence in favor of positively acting transport factors and elements is uncertain at best.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, mutations that alter the regulation of factors involved in splice site selection may also contribute to tumor formation. In addition, GLI1 has been shown to bind RNA directly at a conserved motif that is distinct from the GLI DNA binding cis-element and to regulate translation of the bound mRNA (37,50). Because these putative GLI binding motifs are present in the pre-mRNA sequence of GLI1, an intriguing possibility is that GLI1 itself or a related protein may determine exon selection.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have identified alternative 5Ј UTRs of GLI1 transcripts in mouse and human tissues, which are generated by exon skipping and have marked differences in translation efficiency. Until now, post-transcriptional regulation of GLI1 has been inferred (37), but a precise mechanism has not been determined. Our results suggest that post-transcriptional regulation of GLI1 is mediated by exon skipping and show an association of the most efficiently translated 5Ј UTR transcript with BCC.…”
mentioning
confidence: 99%
“…7A) demonstrated that these promoter elements were also not necessary for the GLI-2/THP effect to occur. tra-1, the GLI protein of C. elegans, has recently been shown to bind to RNA (32). While in C. elegans this binding affected posttranscriptional events, this observation did suggest that GLI-2/THP might interact with RNA elements within the HIV promoters.…”
Section: Gli-2/thp Decreases Expression From the Htlv-1 But Not Htlv-mentioning
confidence: 66%